2019
DOI: 10.1021/acsbiomaterials.8b01390
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Linear Elastic Modulus: Viscoelastic Models for Brain and Brain Mimetic Hydrogels

Abstract: With their high degree of specificity and investigator control, in vitro disease models provide a natural complement to in vivo models. Especially in organs such as the brain, where anatomical limitations make in vivo experiments challenging, in vitro models have been increasingly used to mimic disease pathology. However, brain mimetic models may not fully replicate the mechanical environment in vivo, which has been shown to influence a variety of cell behaviors. Specifically, many disease models consider only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…For example, O. Chaudhuri et al (2016) found out that cells'spreading, proliferation, and osteogenic differentiation of mesenchymal stem cells (MSCs) are all enhanced in cells cultured in gels with faster relaxation [18]. That is why extensive research is devoted to the study of the physicomechanical properties of hydrogels and the development of new methods for assessing these properties [[19], [20], [21], [22], [23]]. Although it is currently difficult to obtain cytocompatible hydrogels with the mechanical properties of native tissues, significant progress has been achieved in the development of materials with custom properties [[24], [25], [26]].…”
Section: Introductionmentioning
confidence: 99%
“…For example, O. Chaudhuri et al (2016) found out that cells'spreading, proliferation, and osteogenic differentiation of mesenchymal stem cells (MSCs) are all enhanced in cells cultured in gels with faster relaxation [18]. That is why extensive research is devoted to the study of the physicomechanical properties of hydrogels and the development of new methods for assessing these properties [[19], [20], [21], [22], [23]]. Although it is currently difficult to obtain cytocompatible hydrogels with the mechanical properties of native tissues, significant progress has been achieved in the development of materials with custom properties [[24], [25], [26]].…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of acoustic pressure, heating, and static displacement in response to radiation force were performed as described previously ( Prieto et al, 2018 ). For simulation of dynamic tissue displacement in response to radiation force, the brain slice was modeled as a incompressible, linear viscoelastic material ( Calhoun et al, 2019 ), characterized by Young’s modulus, Poisson’s ratio, and shear viscosity, loaded by the fluid layer above it. The polystyrene was modeled as a linear elastic material, because we determined in a series of simulations that including viscosity of the polystyrene had no effect on the tissue displacement.…”
Section: Methodsmentioning
confidence: 99%
“…Calculation of the mesh sizes from frequency sweep tests (using Equations ( 3) to ( 6)) is based on the rubber elasticity theory [72]. Although the validity of this theory for gels has continuously been questioned [73,74], it has been repeatedly utilized to calculate the mesh size of hydrogels based on rheometric parameters [52,75]. Previously, we have applied this approach in the determination of mesh size of polysaccharide-based phase-separated hydrogels [76].…”
Section: Characterization Of the Internal Structure Of The Gelsmentioning
confidence: 99%